(untitled) (Nepal Journal of Environmental Science, 2017)
The aim of this study is to determine the knowledge, skill and behavior levels of the individuals, suffering from a disaster, in terms of issues such as survival, finding a safe place, evacuation, first aid, and search and operations as of the first hours following the disaster. Within this scope, 128 students taking disaster awareness training in Vocational School of Health Services in Namık Kemal University of Turkey agreed to participate in this study. The data collection form was prepared by using the preceding studies in literature. The data were analyzed with “SPSS for Windows 15.0”’ package program. Variance analysis, student’s t-test, chi-square test and Pearson correlation test were performed for statistical analyses. The results in which P values were p<0.05 were regarded as statistically meaningful. In this study, it was also analyzed whether there is a relationship between knowledge levels and behavior levels of students in operational issues of disasters or not. In the correlation analysis conducted in this regard, a very strong positive linear relationship was found between the knowledge levels and behavior levels of students (r= 0.762, p <0.001). Education is crucial in providing information to individuals and turning these information into behaviors. The disasters and emergency cases depend upon human behaviors. The disaster awareness trainings and the formation of desired behavior in human beings are shaped on the basis of this. The standards for disaster trainings should be set, and trainings should be provided starting from the earlier ages. Various simulation units should be utilized to improve the persistency of the training content, and trainings should be provided by disaster units. The result shows that the individuals who took disaster training were more effective in determining behavior patterns to be developed during and after disasters.